The Empires Ghost - Steiger, Isabelle 1989- (New York : Thomas Dunne Books/St. Martins Press, 2017)
"The empire of Elesthene once spanned a continent, but its rise heralded the death of magic. It tore itself apart from within, leaving behind a patchwork of kingdoms struggling to rebuild. But when a new dictator, the ambitious and enigmatic Imperator Elgar, seizes power in the old capital and seeks to recreate the lost empire anew, the other kingdoms have little hope of stopping him"-- Provided by publisher.
Keywords: Imaginary places -- Fiction; Imaginary wars and battles -- Fiction; Dictators -- Fiction; Kings and rulers -- Fiction; Fathers and sons -- Fiction; Fantasy fiction